2013
DOI: 10.1155/2013/846584
|View full text |Cite
|
Sign up to set email alerts
|

P53 and Expression of Immunological Markers May Identify Early Stage Thyroid Tumors

Abstract: Background. Besides its major role in cell proliferation, DNA repair, and apoptosis, functional p53 protein is involved in the induction of antitumor cytotoxic-T-cell activity against carcinoma cells. We aimed to investigate p53 and immune cell markers utility as diagnostic and prognostic markers of differentiated thyroid cancer (DTC). Methods. ACIS-III system was used to evaluate p53 and immune cell markers including tumor-associated macrophages (TAM); CD68 and tumor-infiltrating lymphocytes (TIL) subsets suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…[24][25][26][27][28] Some studies showed that the expression of Ki-67 and p53 was not related to tumor size. 42,43 Therefore, the evaluation of the proliferation activity of the tumor cell is more reliable for determining the biological behavior rather than relying on tumor size alone. Indeed, a tumor of 10 mm, for example, can be the results of an aggressive tumor that grew over a few months or of an indolent tumor that grew over a few years.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Some studies showed that the expression of Ki-67 and p53 was not related to tumor size. 42,43 Therefore, the evaluation of the proliferation activity of the tumor cell is more reliable for determining the biological behavior rather than relying on tumor size alone. Indeed, a tumor of 10 mm, for example, can be the results of an aggressive tumor that grew over a few months or of an indolent tumor that grew over a few years.…”
Section: Discussionmentioning
confidence: 99%
“…An IHC study found a significant association of TP53 positivity in TC with thyroiditis [76]. Increased apoptosis was detected in a case series of HT and thyroid tumors, and it was noted that elevated TP53 and/or CDKN1A protein expression is an indication for possible DNA damage and enhanced apoptosis in HT [77].…”
Section: The 950 Deg Set From the Intersection Of All Four Comparisonmentioning
confidence: 99%
“…Previous findings have indicated that tumour development involves a series of mutation of molecules, including oncogenes and tumour suppressor genes 47. Presently, the use of these molecules as markers in the diagnostic and prognostic management of PTC is increasing 8,9. Puli provided evidence suggesting that ETV5 and its putative target CCND1/2 may be proliferative markers of advanced PTC 10.…”
Section: Introductionmentioning
confidence: 99%